(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The accounting system of government is considered an important tool to follow up the financial transactions that reflect the activities of governmental units and by which the useful information for estimating governmental annual revenues and expenditures are provided through the state public budget because it is an information system that provides detailed past performance, as well as measures the efficiency of the governmental agencies performance in implementing the budget, and the of success governmental units is measured through the type of services and programs offered, their size and the possibility of achieving the objectives assigned to them. The medical evacuation program is one of the medical and curative health services provided by the Ministry of Health through deporting intractable cases for the treatment outside the country and treating the pathological cases which can be treated in hospitals within the country at the expense of the state, hosting the foreign medical teams with expertise in all specializations and also exchanging of experiences with Iraqi specialized doctors. The research aims to provide a theoretical and practical background for medical evacuation program, review the deficiencies in the actual implementation of the program and the determinants to develop it and propose a model to audit the program that helps to improve the effectiveness of the control system. The research was based on two hypotheses. The first is "that the existence of effective tools for controlling the medical programs ensures effective utilization of available resources". The second is "that addressing the shortcomings in the implementation of medical evacuation program leads to the expansion of implementation scope." The research addresses the theoretical framework of the governmental accounting system, the medical evacuation program and the shortcomings in implementing the program and a model has been proposed to audit the medical evacuation program, which contributes to tackle the deficiencies in the administrative, financial and technical aspects. In light of the theoretical and practical study a set of conclusions has been reached and recommendations.